2021
DOI: 10.1155/2021/6676689
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparative Study of Compact Multiband Bio-Inspired Asymmetric Microstrip Fed Antennas (BioAs-MPAs) for Wireless Applications

Abstract: A comparative analysis of compact multiband bio-inspired Asymmetric microstrip fed antennas (BioAs-MPAs) is presented in this paper for the first time. The proposed antennas are based on semi-Carica papaya-leaf shaped, semi-Monstera deliciosa-leaf shaped, semi-Vitis vinifera shaped, Defected Ground Structure (DGS) and L-slit techniques. The antennas are built on a 33 × 15 mm2 Rogers duroid 5880 substrate. The modelling equations for resonant frequencies of the proposed arbitrarily shaped radiating patch is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Many techniques have been explored in the literature for the miniaturization of multiband antennas. For example, slotting [1,2,3,4,5], Defected ground structure (DGS) [6,7,8,9], parasitic loading [6,10,11,12,13,14,15], and multiple structure techniques have been used. Some of these structures have their disadvantages, for example, slotting (on the radiating patch) reduces the antenna gain and radiation efficiency; DGS can lead to complex structure; parasitic loading and multiple structure techniques increase the antenna size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many techniques have been explored in the literature for the miniaturization of multiband antennas. For example, slotting [1,2,3,4,5], Defected ground structure (DGS) [6,7,8,9], parasitic loading [6,10,11,12,13,14,15], and multiple structure techniques have been used. Some of these structures have their disadvantages, for example, slotting (on the radiating patch) reduces the antenna gain and radiation efficiency; DGS can lead to complex structure; parasitic loading and multiple structure techniques increase the antenna size.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, the bio-inspired structure has also attracted antenna engineers due to its advantages such as perimeter improvement, fractality (self-repeating) nature, and flexibility. Whereas, majority of the bio-inspired antennas reported in the literature focus on ultrawideband applications [ 18 , 19 , 20 , 21 , 22 ], others have also explored it in developing compact multi-band antennas [ 4 , 5 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…e same meandering technique has been recently exploited by authors in [5][6][7][8]. Furthermore, the slotting technique has been used by authors in [2,[20][21][22][23][24][25]. For example, authors in [20] used the Audi logo-shaped as a slot on a rectangular patch on a 20 × 12 mm 2 FR-4 substrate to achieve a triband antenna operating at 3.9 GHz, 5.0 GHz, and 7.1 GHz, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the same light, authors in [15] have also used metasurface to achieve 67% miniaturization. In recent times, folded monopole antenna has attracted antenna design engineers due to its ability to reduce overall antenna size [25][26][27][28][29][30][31][32][33][34]. Folded monopole antenna uses the principle of space filling to miniaturize the antenna radiating patch.…”
Section: Introductionmentioning
confidence: 99%
“…In the article titled "A Comparative Study of Compact Multiband Bio-Inspired Asymmetric Microstrip Fed Antennas (BioAs-MPAs) for Wireless Applications" [1], the authors identified an error in equation ( 1), and the corrected equation is as follows:…”
mentioning
confidence: 99%